PENGARUH E-SERVICE QUALITY, ONLINE CUSTOMER REVIEW, DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE - Febrianti Muji Trianawati; Adi Santoso; Eka Destriyanto Pristi (STIE Trisna Negara OKU Timur, 2022)
The advancement of a technological development in this digital era is certainly getting faster, especially the internet. The development of the internet is of course not only for communication but also used for purchasing goods, ordering transportation to doing business, working and also being used for various purposes. This study aims to see the effect of e-service quality, online customer reviews, and online customer ratings on purchasing decisions on e-commerce Shopee. The population of this research is Muhammadiyah University Ponorogo students who have made purchasing decisions on Shopee e-commerce. The sampling technique using accidental sampling is known to be all 95 samples and to collect data through questionnaires and processed with SPSS version 25. For this study, the results of e-service quality, online customer reviews, and online customer ratings have a significant effect on purchasing decisions.